Imidazolyl composite material, preparation method and application thereof, and flexible aqueous zinc ion battery

CN116864681BActive Publication Date: 2026-10-16SHIHEZI UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310735057.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-16
Publication Date
2026-10-16
Estimated Expiration
2043-06-16

AI Technical Summary

Technical Problem

公开号为CN110534711A的中国专利公开了一种水系电池用聚酰亚胺正极材料,但其采用加热回流法进行合成,工艺复杂且需要高温高压的条件,对于生产设备的要求比较高,不适合工业化生产

Benefits of technology

[0022] This invention provides a method for preparing an imidazole-based composite material, comprising the following steps: mixing an acid anhydride and a diamino compound, and carrying out a solid-state reaction under a protective atmosphere to obtain the imidazole-based composite material. This invention allows for the one-step heat treatment of the acid anhydride and diamino compound to obtain the desired imidazole-based composite material, resulting in a simple, low-cost, and mild reaction condition suitable for industrial production. In the imidazole-based composite material obtained by the method provided by this invention, the expanded π-conjugated structure can improve the degradation problem faced by small anhydride molecules, while the stable framework can enhance the cycling performance of the material. Furthermore, the flexible framework ensures the stability of the material under different current densities and exhibits excellent bending resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116864681B_ABST
    Figure CN116864681B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of zinc ion batteries, and particularly relates to an imidazole-based composite material, a preparation method and application thereof, and a flexible aqueous zinc ion battery. The application provides a preparation method of the imidazole-based composite material, which comprises the following steps: mixing an anhydride and a diamino compound, and performing a solid phase reaction under a protective atmosphere to obtain the imidazole-based composite material. The anhydride and the diamino compound can obtain the required imidazole-based composite material through one-step heat treatment, the preparation method is simple, the cost is low, the reaction condition is mild, and the method is suitable for industrial production. In the imidazole-based composite material obtained by the preparation method, the expanded pi conjugated structure can improve the attenuation problem of the anhydride small molecule, and the stable skeleton can improve the cycle performance of the material. In addition, the flexible skeleton ensures the stability of the material under different current densities, and the material has good bending resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of zinc-ion battery technology, specifically relating to an imidazole-based composite material, its preparation method and application, and a flexible aqueous zinc-ion battery. Background Technology

[0002] Lithium-ion batteries are widely used in daily life due to their advantages such as high energy density, high voltage, and wide operating temperature range. However, lithium-ion batteries use organic solvents as electrolytes, which are flammable and volatile, posing serious safety risks.

[0003] Aqueous zinc-ion batteries are ideal for energy storage devices due to their high safety, low cost, and high theoretical capacity. As a component of aqueous zinc-ion batteries, the cathode material plays a crucial role. Compared to inorganic materials, organic compounds are widely available, structurally diverse, environmentally friendly, and low-cost, making them suitable for preparing battery electrode materials.

[0004] Acid anhydride compounds possess suitable redox potentials, making them suitable for use as electrodes in ion-ion batteries. However, issues such as easy solubility of the active materials, poor conductivity, and low specific capacity lead to rapid capacity decay in batteries. Therefore, developing high-capacity and high-stability zinc storage cathode materials based on acid anhydrides is of great significance.

[0005] In current research, acid anhydride molecules are often polymerized with amino compounds to form polyimides. Chinese patent CN110534711A discloses a polyimide cathode material for aqueous batteries, but it is synthesized using a heating reflux method, which is complex and requires high-temperature and high-pressure conditions, placing high demands on production equipment and making it unsuitable for industrial production. Summary of the Invention

[0006] The purpose of this invention is to provide an imidazole-based composite material, its preparation method and application, and a flexible aqueous zinc-ion battery. The method provided by this invention has a simple preparation process and mild reaction conditions, making it suitable for industrial production.

[0007] To achieve the above objectives, the present invention provides the following technical solution:

[0008] This invention provides a method for preparing an imidazole-based composite material, comprising the following steps:

[0009] An acid anhydride and a diamino compound are mixed and subjected to a solid-phase reaction under a protective atmosphere to obtain the imidazole-based composite material.

[0010] Preferably, the acid anhydride includes one or more of pyromellitic dianhydride, naphthalenetetracarboxylic dianhydride, and perylenetetracarboxylic dianhydride.

[0011] Preferably, the diamino compound includes one or more of diaminoanthraquinone, diaminonaphthoquinone, diaminophenazine, diaminobenzoic acid, and diaminobenzoquinone.

[0012] Preferably, the molar ratio of the acid anhydride to the diamino compound is 1:1 to 2.

[0013] Preferably, the solid-phase reaction is carried out at a temperature of 300–350°C for 4–12 hours.

[0014] Preferably, after the solid-phase reaction, the resulting material is further subjected to sequential washing and drying;

[0015] The organic solvents used for cleaning include ethanol, N-methylpyrrolidone, or N,N-dimethylformamide;

[0016] The drying temperature is 60–80°C, and the time is 6–12 hours.

[0017] The present invention also provides an imidazole-based composite material prepared by the preparation method described in the above technical solution.

[0018] The present invention also provides the application of the imidazole-based composite material described in the above technical solution in an aqueous zinc-ion battery.

[0019] The present invention also provides a flexible aqueous zinc-ion battery, wherein the positive electrode material of the flexible aqueous zinc-ion battery includes the imidazole-based composite material described in the above technical solution.

[0020] Preferably, the electrolyte of the flexible aqueous zinc-ion battery is a Zn(CF3SO3)2 gel electrolyte or a ZnSO4 gel electrolyte;

[0021] The concentration of the electrolyte is 1 mol / L.

[0022] This invention provides a method for preparing an imidazole-based composite material, comprising the following steps: mixing an acid anhydride and a diamino compound, and carrying out a solid-state reaction under a protective atmosphere to obtain the imidazole-based composite material. This invention allows for the one-step heat treatment of the acid anhydride and diamino compound to obtain the desired imidazole-based composite material, resulting in a simple, low-cost, and mild reaction condition suitable for industrial production. In the imidazole-based composite material obtained by the method provided by this invention, the expanded π-conjugated structure can improve the degradation problem faced by small anhydride molecules, while the stable framework can enhance the cycling performance of the material. Furthermore, the flexible framework ensures the stability of the material under different current densities and exhibits excellent bending resistance. Attached Figure Description

[0023] Figure 1 Here is a SEM image of the imidazole-based composite material obtained in Example 1;

[0024] Figure 2 The infrared spectrum of the imidazole-based composite material obtained in Example 1;

[0025] Figure 3 The constant current charge-discharge curve of the aqueous zinc-ion battery assembled from the imidazole-based composite material obtained in Example 1 is shown.

[0026] Figure 4 The rate performance curve of the aqueous zinc-ion battery assembled from the imidazole-based composite material obtained in Example 1 is shown.

[0027] Figure 5 The cycling performance curve of the aqueous zinc-ion battery assembled from the imidazole-based composite material obtained in Example 1 is shown.

[0028] Figure 6 The bending resistance test curve is shown for the aqueous zinc-ion battery assembled from the imidazole-based composite material obtained in Example 1. Detailed Implementation

[0029] This invention provides a method for preparing an imidazole-based composite material, comprising the following steps:

[0030] An acid anhydride and a diamino compound are mixed and subjected to a solid-phase reaction under a protective atmosphere to obtain the imidazole-based composite material.

[0031] In this invention, unless otherwise specified, all raw materials used in the preparation are commercially available products well known to those skilled in the art.

[0032] In this invention, the acid anhydride preferably includes one or more of pyromellitic dianhydride, naphthalenetetracarboxylic dianhydride, and perylenetetracarboxylic dianhydride. In this invention, the diamino compound preferably includes one or more of diaminoanthraquinone, diaminonaphthoquinone, diaminophenazine, diaminobenzoic acid, and diaminobenzoquinone.

[0033] In this invention, the molar ratio of the acid anhydride and the diamino compound is preferably 1:1 to 2, and more preferably 1:1.3 to 1.5.

[0034] The present invention does not impose any particular limitation on the mixing process; any process well known to those skilled in the art can be used. In a specific embodiment of the present invention, the mixing method is preferably grinding in a mortar.

[0035] In this invention, the temperature of the solid-phase reaction is preferably 300–350°C, more preferably 310–340°C, and even more preferably 320–330°C; the time is preferably 4–12 h, more preferably 5–10 h, and even more preferably 6–8 h. In this invention, the protective atmosphere is preferably nitrogen or argon. In this invention, the solid-phase reaction is preferably carried out in a tube furnace. In this invention, during the solid-phase reaction, the carbonyl group in the acid anhydride reacts with the two amino groups in the amino compound to form an imidazole ring, thereby expanding the conjugated structure of the material and forming a stable structure.

[0036] Following the solid-phase reaction, the present invention preferably further includes sequentially washing and drying the obtained material. In this invention, the organic solvent used for washing preferably includes ethanol, N-methylpyrrolidone, or N,N-dimethylformamide. The present invention does not impose any particular limitation on the washing process; any process well known to those skilled in the art can be used. In this invention, the drying temperature is preferably 60–80°C, and the drying time is preferably 6–12 hours.

[0037] The present invention also provides an imidazole-based composite material prepared by the preparation method described in the above technical solution.

[0038] The present invention also provides the application of the imidazole-based composite material described in the above technical solution in an aqueous zinc-ion battery.

[0039] The present invention also provides a flexible aqueous zinc-ion battery, wherein the positive electrode material of the flexible aqueous zinc-ion battery includes the imidazole-based composite material described in the above technical solution.

[0040] In this invention, the positive electrode material of the aqueous zinc-ion battery preferably includes a conductive agent and a binder; the conductive agent preferably includes Ketjen black, and the binder preferably includes polyvinylidene fluoride; the mass ratio of the imidazole-based composite material, Ketjen black, and polyvinylidene fluoride is preferably 6:3:1.

[0041] In this invention, the electrolyte of the flexible aqueous zinc-ion battery is preferably a Zn(CF3SO3)2 gel electrolyte or a ZnSO4 gel electrolyte; the concentration of the electrolyte is 1 mol / L. In this invention, the dispersion medium of the electrolyte is preferably polyvinyl alcohol.

[0042] To further illustrate the present invention, the following detailed description, in conjunction with the accompanying drawings and embodiments, provides an imidazole-based composite material, its preparation method and application, and a flexible aqueous zinc-ion battery, but these descriptions should not be construed as limiting the scope of protection of the present invention.

[0043] Example 1

[0044] Naphthalenetetracarboxylic dianhydride and diaminophenazine are ground in a mortar at a molar ratio of 1:2 to form a homogeneous mixture;

[0045] The obtained mixture was placed in a ceramic boat and placed in a tube furnace under a nitrogen inert atmosphere. The solid-phase reaction was carried out at 350°C for 4 hours. The obtained solid powder was washed with N-methylpyrrolidone and dried in a vacuum drying oven at 80°C for 12 hours to obtain the imidazole-based composite material.

[0046] Example 2

[0047] Naphthalenetetracarboxylic dianhydride and diaminoanthraquinone were ground in a mortar at a molar ratio of 1:2 to form a homogeneous mixture.

[0048] The obtained mixture was placed in a ceramic boat and placed in a tube furnace under a nitrogen inert atmosphere. The solid-phase reaction was carried out at 350°C for 4 hours. The obtained solid powder was washed with N-methylpyrrolidone and dried in a vacuum drying oven at 80°C for 12 hours to obtain the imidazole-based composite material.

[0049] Example 3

[0050] Pyromellitic dianhydride and diaminoanthraquinone were ground in a mortar at a molar ratio of 1:2 to form a homogeneous mixture.

[0051] The obtained mixture was placed in a ceramic boat and placed in a tube furnace under a nitrogen inert atmosphere. The solid-phase reaction was carried out at 350°C for 4 hours. The obtained solid powder was washed with N-methylpyrrolidone and dried in a vacuum drying oven at 80°C for 12 hours to obtain the imidazole-based composite material.

[0052] Example 4

[0053] Perylenetetracarboxylic dianhydride and diaminoanthraquinone were ground in a mortar at a molar ratio of 1:2 to form a homogeneous mixture;

[0054] The obtained mixture was placed in a ceramic boat and placed in a tube furnace under a nitrogen inert atmosphere. The solid-phase reaction was carried out at 350°C for 4 hours. The obtained solid powder was washed with N-methylpyrrolidone and dried in a vacuum drying oven at 80°C for 12 hours to obtain the imidazole-based composite material.

[0055] Example 5

[0056] Naphthalenetetracarboxylic dianhydride and diaminobenzoic acid are ground in a mortar at a molar ratio of 1:2 to form a homogeneous mixture;

[0057] The obtained mixture was placed in a ceramic boat and placed in a tube furnace under a nitrogen inert atmosphere. The solid-phase reaction was carried out at 350°C for 4 hours. The obtained solid powder was washed with N-methylpyrrolidone and dried in a vacuum drying oven at 80°C for 12 hours to obtain the imidazole-based composite material.

[0058] Performance testing

[0059] Test Example 1

[0060] Figure 1 The image shows a SEM image of the imidazole-based composite material obtained in Example 1. Figure 1 It can be seen that the obtained imidazole-based composite material exhibits a stacked structure with a size of 200–300 nm;

[0061] Figure 2 The infrared spectrum of the imidazole-based composite material obtained in Example 1 is shown below. Figure 2 It can be seen that the imidazole-based composite material at 534 cm⁻¹ -1 There is a characteristic peak generated by OV bonds at 1098 cm⁻¹. -1 There is a characteristic peak generated by CO bonds at 1495 cm⁻¹. -1 The presence of a sharp characteristic peak resulting from a C=O bond indicates the successful synthesis of the compound.

[0062] Test Example 2

[0063] Using the imidazole-based composite materials obtained in Examples 1-5 as positive electrode active materials, aqueous zinc-ion batteries were assembled and their electrochemical performance was tested.

[0064] The positive electrode active material, Ketjen black, and polyvinylidene fluoride (PVDF) were mixed and ground in a mass ratio of 6:3:1. The resulting mixture was then dispersed in N-methylpyrrolidone (NMP), and the resulting slurry was coated on a stainless steel mesh. Subsequently, it was vacuum dried at 80°C for 12 hours, and then punched into an electrode sheet with a diameter of 10 mm using a slicing machine.

[0065] A CR2032 coin cell was assembled using 1.0M Zn(CF3SO3)2 gel electrolyte, glass fiber filter paper as the diaphragm, and a zinc sheet as the counter electrode; the charge / discharge potential was set in the range of 0.05–1.5V.

[0066] At 0.05 A·g -1 The test results of the discharge specific capacity at the given current density are shown in Table 1.

[0067] Table 1. Specific capacity test results of batteries assembled from imidazole-based composite materials in Examples 1-5.

[0068]

[0069] Figure 3 The aqueous zinc-ion battery assembled from the imidazole-based composite material obtained in Example 1 was tested at 0.05 A·g. -1 The constant current charge-discharge curve at the current density; from Figure 3 It can be seen that the specific capacity of the first discharge cycle is 318 mAh·g. -1 The tenth cycle is 289mAh·g -1 The thirtieth cycle is 273mAh·g -1 The fiftieth cycle is 265mAh·g -1 .

[0070] Figure 4 The graph shows the rate performance of an aqueous zinc-ion battery assembled from the imidazole-based composite material obtained in Example 1; from Figure 4 It can be seen that the imidazole-based composite material provided by the present invention has excellent rate performance;

[0071] Figure 5 The graph shows the cycle performance of an aqueous zinc-ion battery assembled from the imidazole-based composite material obtained in Example 1; from Figure 5 It can be seen that the imidazole-based composite material provided by this invention has a performance of 15 A·g -1 At ultra-high current density, the specific capacity can reach 200 mAh·g -1 The capacity can still be maintained after 300 cycles, indicating that it still has excellent cycle performance under ultra-high current density, and can be used to prepare the positive electrode of long-life aqueous zinc-ion battery.

[0072] Test Example 3

[0073] The bending resistance of the aqueous zinc-ion battery assembled from the imidazole-based composite material obtained in Example 1 was tested. The test method was as follows: at 3 A·g -1 Specific capacity was tested at different bending angles under different current densities;

[0074] The test results obtained are as follows Figure 6 As shown, from Figure 6 It can be seen that the flexible aqueous zinc-ion battery assembled with the imidazole-based composite material obtained in this invention has excellent bending resistance, and the specific capacity in the initial state is 139 mAh·g. -1 ; 136 mAh·g when bent at 45° -1 ; 128mAh·g when bent at 90° -1 ; 119 mAh·g when bent at 135° -1 ; 112 mAh·g when bent 180° -1 In summary, the flexible zinc-ion battery assembled from the imidazole-based composite material obtained by this invention exhibits excellent bending resistance.

[0075] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. Other embodiments can be obtained based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing an imidazole-based composite material, characterized in that, Includes the following steps: An acid anhydride and a diamino compound are mixed and subjected to a solid-phase reaction under a protective atmosphere to obtain the imidazole-based composite material. The acid anhydride includes one or more of pyromellitic dianhydride, naphthalenetetracarboxylic dianhydride, and perylenetetracarboxylic dianhydride; The diamino compound includes one or more of diaminoanthraquinone, diaminonaphthoquinone, diaminophenazine, diaminobenzoic acid, and diaminobenzoquinone; The solid-phase reaction is carried out at a temperature of 300-350℃ for 4-12 hours.

2. The preparation method according to claim 1, characterized in that, The molar ratio of the acid anhydride to the diamino compound is 1:1~2.

3. The preparation method according to claim 1, characterized in that, The solid-phase reaction is followed by sequential washing and drying of the resulting material; The organic solvents used for cleaning include ethanol, N-methylpyrrolidone, or N,N-dimethylformamide; The drying temperature is 60~80℃, and the time is 6~12h.

4. The imidazole-based composite material prepared by the preparation method according to any one of claims 1 to 3.

5. The application of the imidazole-based composite material according to claim 4 in an aqueous zinc-ion battery.

6. A flexible aqueous zinc-ion battery, characterized in that, The positive electrode material of the flexible aqueous zinc-ion battery includes the imidazole-based composite material as described in claim 4.

7. The flexible aqueous zinc-ion battery according to claim 6, characterized in that, The electrolyte of the flexible aqueous zinc-ion battery is Zn(CF3SO3)2 gel electrolyte or ZnSO4 gel electrolyte; The concentration of the electrolyte is 1 mol / L.

Citation Information

Patent Citations

  • Preparation method of polyimide composite material and application of polyimide composite material in battery

    CN110534711A

  • Organic electrode material of organic electrolyte sodium iron battery and preparation method thereof

    CN106328949A

  • PMDQ, NTDQ and PTDQ as well as preparation method and application thereof

    CN116082345A